(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The paper broadly examined counter-insurgency, and narrowed it downed to counter-terrorism efforts and inhibitors using Nigeria and the Boko Haram sect as the core study area and subject, respectively. It sought to integrate and synchronize the political, security, economic and informational components as veritable factors in countering subversion and violence of all sorts by sects. Agreeing that government must seize initiative, have overall plan, clear political aim, act in accordance with the dictates of the law, and give priority to defeating political subversion, all efforts, so far, geared towards defeating Boko Haram in Nigeria did not yield results. The paper concluded that all military and non-military measures were undermined by poor inter-agency cooperation and coordination; poor inter-agency intelligence information management; poor civil-military relations; and funding constraints and corruption in Defense Budgetary processes and arms procurement. The paper was written with primary documents and commentaries. Secondary sources served complementary purposes.